(untitled) (European Journal of Social Science Education and Research, 2023)
In the 21st century, parenting has become increasingly complex. With a vast array of technology and resources available to parents, it is important for them to understand how best to use these tools to raise healthy and successful children. The advent of technology and the internet has changed the way we live and interact with each other, and it has also influenced the way we raise our children. In this article, it will be compared and discussed the differences between parenting in the 21st century and in previous centuries. The article will provide an overview of how technology and other cultural factors have impacted the way we raise our children, and how this has affected the children's development. In addition, there are many new challenges that face parents today such as cyberbullying, social media addiction and mental health issues which require special attention from parents. This article will discuss some key strategies for effective parenting in the 21st century including setting boundaries, staying connected with your child’s activities online and offline, being aware of potential dangers online and monitoring their behavior while also providing support when needed. It will also explore ways that modern technologies can be used effectively by both parents and children alike to foster positive relationships between family members. Finally, this article will provide advice on how best to cope with common parenting problems associated with raising kids in the digital age so families can enjoy all of its benefits without sacrificing safety or security.